Effect of spillway-ogee location on flow uniformity and turbulence at the crest of an ogee weir - Alsultan, Faisal Abdulaziz, author; Ettema, Robert, advisor; Thornton, Christopher, committee member; Conrad, Steven A., committee member (Colorado State University. Libraries, 2023)
This study investigated the effect of spillway-crest location relative to spillway entrance, and spillway-abutment shape, on uniformity of flow distribution and turbulence intensity of flow, over the ogee crest of a spillway. These issues are especially of concern for spillways for which the approach flow to the ogee weir is relatively shallow. Circular and elliptical shapes of abutments were used. These abutment forms, and the bathymetry of the reservoir approach to the spillway, cause the approach flow to the ogee weir to be non-uniformly distributed and turbulent for part of the ogee weir. Turbulence can be generated by flow separation from an abutment or by the manner whereby the flow approaches the spillway. In the latter case, the reservoir bathymetry at the spillway entrance is important, as it affects flow distribution at the spillway entrance. The base spillway used for the study was a hydraulic model used to assist in the design of the new spillway for Los Vaqueros Dam on Kellogg Creek near Brentwood, California. The flow approach to this spillway is typical of many, relatively shallow over-flow spillways that involve an ogee crest. As often is the case for spillways associated with embankment dams, the spillway is built on an abutment of the dam itself and must deal with non-uniform and turbulent approach flow from the reservoir retained by the dam to the spillway's location at the side of the dam. Consequently, the approach flow was non uniform and turbulent, and design questions arise as to where to place the ogee crest for the spillway and what shape to use for a spillway. Though the investigation used the spillway just mentioned, the results have general application. The experiments were performed using a spillway flume with a rectangular cross-section, a circular abutment intake and a controllable spillway crest with changing the crest location to five locations (one downstream of the selected location and three upstream of that location). Measurements included water profiles, velocity across transects downstream of the spillway's entrance. These measurements were made for a circular spillway-abutment and for an elliptical spillway-abutment. The results show that changing the crest location significantly affects flow uniformity and possible shed-vortex formation from the intake abutment. Therefore, the results also indicate that spillway crest location has a direct impact on the hydraulic performance of the spillway. Suitable selection of crest location can be used to minimize non-uniformity and vortex-related problems in spillway design. The present study recommends that the ogee crest face be placed at least 1.5 crest widths from the entrance of the spillway. This position enables the flow to the crest to become suitably uniform and turbulence of flow within the entrance to extensively (though not entirely) decay. The findings from this study are significant for engineers and researchers involved in spillway design and generally in many aspects of hydraulic engineering design. The findings also demonstrate the importance of careful consideration of crest location in spillway design to mitigate problems related to vortex formation. Overall, this study adds to the knowledge base regarding spillways and their design. Spillways have been used for hundreds of years but there are many aspects of these hydraulic structures requiring continued research.